2017
DOI: 10.1016/j.jpainsymman.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Collusions Between Patients and Clinicians in End-of-Life Care: Why Clarity Matters

Abstract: Collusion, an unconscious dynamic between patients and clinicians, may provoke strong emotions, unreflected behaviors, and a negative impact on care. Collusions, prevalent in the health care setting, are triggered by situations which signify an unresolved psychological issue relevant for both, patient and clinician. After an introductory definition of collusion, two archetypal situations of collusion-based on material from a regular supervision of a palliative care specialist by a liaison psychiatrist-and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…To the Editor Burnout is a real concern for palliative care practitioners (PCPs) regularly caring for seriously ill patients and families. 1 In our previous study, we found the prevalence of burnout to be 33% among PCPs in Singapore. 2 A recent study showed the prevalence among U.S. palliative care clinicians 3 to be as high as 62%.…”
Section: Clinical Variety May Help Prevent Burnout After a Decade In mentioning
confidence: 92%
See 3 more Smart Citations
“…To the Editor Burnout is a real concern for palliative care practitioners (PCPs) regularly caring for seriously ill patients and families. 1 In our previous study, we found the prevalence of burnout to be 33% among PCPs in Singapore. 2 A recent study showed the prevalence among U.S. palliative care clinicians 3 to be as high as 62%.…”
Section: Clinical Variety May Help Prevent Burnout After a Decade In mentioning
confidence: 92%
“…It provokes intense emotions and/or unreflected behaviors. 1,2 For example, a patient with great difficulties coping with separation, due to prior life events (early losses), faces death and, consequently, separation from loved ones. He requests assisted suicide, arguing that he is tired of life; he is not aware that the request is motivated by his desire to hasten separation, a process he greatly fears (to ''get it over with'').…”
Section: Why Collusion Matters?mentioning
confidence: 99%
See 2 more Smart Citations
“…This objective also requires methods that enable or enhance introspection, since clinician's own emotions, perceptions and attitudes potentially erect barriers between the clinician and the patient. Outer barriers, such as those discussed under section 3.5 (study of Dencker et al, 2017), utilised for defensive purposes by clinicians, can also be addressed and modified by means of methods facilitating introspection, such as individual and group supervisions or Balint-inspired groups (Stiefel, Nakamura, Terui, & Ishitani, 2017). Such a clinician-centred approach, which has recently been endorsed by the third European consensus meeting on communication in cancer care, has the concurrent advantages of (a) being generic, in the sense that it is not a situation-specific approach, multiplying training methods related to different topics; (b) stimulating a reflective process, which benefits the clinician and the patient; (c) directly addressing participants' individual resources and possibilities; and (d) limiting the amount of predefined communication behaviours to be acquired.…”
Section: Practice Implicationsmentioning
confidence: 99%